Design, feasibility, and acceptability of an intervention using personal digital assistant-based self-monitoring in managing type 2 diabetes - Sevick, Mary Ann (2007)
BACKGROUND: The information processing demands associated with behavioral self-management of diabetes are extensive. Pairing personal digital assistant (PDA)-based self-monitoring with a behavioral self-management intervention may improve adherence and patient outcomes. METHODS: ENHANCE is a randomized controlled trial to test an intervention designed to improve regimen adherence in adults with type 2 diabetes. The intervention, based on Social Cognitive Theory (SCT), is paired with PDA-based self-monitoring. In this paper we describe the: (a) manner in which PDA-based self-monitoring is integrated within the SCT-based intervention, (b) feasibility and acceptability of PDA-based dietary self-monitoring, and (c) issues encountered in teaching participants to self-monitor using a PDA. RESULTS: During the first 30 months of this 5-year study, 232 participants were screened and 151 were randomized. To date, 6 cohorts have completed the study. The retention rate is 85% (n=129). Of those randomized to the intervention (n=74) and completing the study (n=61), 88% reported understanding the usefulness of PDA-monitoring, 85% reported ease in entering foods into the device, 70% reported ease in interpreting feedback graphs, and 82% indicated that they would continue to use the PDA for self-monitoring after the study concluded. Assuming 3 meals per day, participants entered an average of 58% of their meals in their PDA, and 43% were entered assuming 4 meals per day. If we eliminate from the analysis those individuals who entered less than 10% of their expected meals (n=12), the average rate of self-monitoring was 69% assuming 3 meals per day, and 52% assuming 4 meals per day. CONCLUSIONS: PDA-based dietary monitoring is perceived by participants to be useful and acceptable. The approach used to instruct participants in use of the PDA and lessons learned are discussed. PDA technology shows promise as a tool for assisting those with type 2 diabetes in their efforts to manage their disease.